Pembuatan taman baca WA Pesek Hutan Kanal Kecamatan Medan Johor - Sukarsih; Aryo Bimo Setya Permana; Tuah Panjaitan (LPPM Universitas Al-Azhar medan, 2024)
The implementation of community service has a specific goal, namely to raise awareness about the importance of reading among school students and utilize the Hutan Kanal land by constructing a reading garden for the community. This activity is carried out in collaboration with the Community Care Association (WA PESEK), a partner with legal status located at Jl. Karya Jaya No. 136 Pangkalan Mansyur, Medan Johor Subdistrict. This community service plays a crucial role as an educational garden for students and the surrounding community, with the hope of making a positive contribution to enhancing reading interest and sustainable utilization of the Hutan Kanal land